Against absolute goodness - Kraut, Richard, 1944- (New York ; Oxford : Oxford University Press, 2011)
Are there things we should value because they are, quite simply good? Richard Kraut argues that there are not. Goodness, he holds, is not a reason-giving property - in fact, there may be no such thing. It is an illusory and insidious category of practical thought.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Good and evil